Barça Innovation Hub : getting the ball rolling on innovation - Chesbrough, Henry; Visnjic, Ivanka; Mundet, Albert; Volwahsen, George (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2021)
This case study follows the Spanish football club, FC Barcelona, as it starts to innovate and create an organizational structure for open innovation.
Originally Published InChesbrough, H., Visnjic, I., Mundet, A., & Volwahsen, G. E. (2021). Barça Innovation Hub: Getting the Ball Rolling on Innovation. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Futbol Club Barcelona -- Case studies; Organizational change -- Case studies